Zircon U–Pb dating and phase equilibria modelling of gneisses from Dinggye area, Ama Drime Massif, central Himalaya - Wang, Yu‐Hua; Zhang, Li‐Fei; Li, San‐Zhong; Somerville, Ian; Suo, Y. (Geological journal (Chichester, England), 2017)
The tectonic affinity of the Ama Drime Massif in central Himalaya remains a subject of debate. We provide evidences of the metamorphic conditions and new geochronological data for orthogneiss and paragneiss in the Riwu area, eastern side of Ama Drime Massif. The peak P–T conditions for garnet gneiss is 13–14 kbar and 750–765 °C using phase equilibria modelling. The zircon U–Pb dating results reveal that the orthogneiss has a crystallization age of 1,848 ± 12 Ma and zircon rims age of 1,767 ± 18 Ma. Three major age peaks characterize all detrital zircons from the paragneisses: 975, 1,161, and 1,749 Ma. These new data integrated with previous literature data indicate that (a) the Ama Drime Massif might be ascribed to the Greater Himalayan Series; and (b) the Himalayan terrane may have been located closer to both the India and Lhasa terranes during the amalgamation of the supercontinent Columbia.